Formation and Assessment of Skills of Independent Preparation of Written Works in General - O. A. Vakurova; O. A. Filippova (Открытое образование (Москва))
Purpose of research. Today, the informatization of school education has reached a qualitatively new level, schools now have access to fast Internet, modern computer equipment, etc. However, the quality of independent written work of students may significally fall, due to open and free access to fabricated texts (essays, reports, essays), as well as the lack of basic skills of independent work and curiosity among the younger generation. In this regard, the purpose of the study is to pose the problem of formation and evaluation of skills for independent preparation of written work in General education, to consider the current state of affairs in this area of primary education, to develop proposals and solutions to this problem.Materials and methods. To solve this problem, the authors of the article have analyzed the works of Russian and foreign authors in the field of pedagogy, as well as works on the digital generation and the information society formation in the Russian Federation and legislative acts (Federal law «on education in the Russian Federation» dated 29.12.2012 N 273-FZ, national project «Education», order of the Ministry of education and science of the Russian Federation dated December 17, 2010 No. 1897 «on approval of the Federal state educational standard of basic General education», The procedure for admitting citizens to study in educational programs of primary General, basic General and secondary General education, approved by order of the Ministry of education and science of the Russian Federation of January 22, 2014, No. 32, etc.).Results. The study has revealed the current situation in teaching and explaining the basic skills of independent and creative work of students: the lack of methodological foundations and practice of teaching the basics of academic ethics and academic writing, the lack of automated means of monitoring the independent performance of written works.Conclusion. In the article, the authors provide basic recommendations and suggestions for improving the current situation, such as the introduction of elements of informing the school system about the requirements for independence in the performance of educational work as part of academic ethics, elements of independence control (systems for detecting borrowings in written works), the development of programs for teachers to master the means of controlling the independence of students’ written work.